In vivo experimental study of anterior cervical fusion using bioactive polyetheretherketone in a canine model. - Takayoshi Shimizu; Shunsuke Fujibayashi; Seiji Yamaguchi; Bungo Otsuki; Yaichiro Okuzu; Tomiharu Matsushita; Tadashi Kokubo; Shuichi Matsuda (PLoS ONE)
Background Polyetheretherketone (PEEK) is a widely accepted biomaterial, especially in the field of spinal surgery. However, PEEK is not able to directly integrate with bone tissue, due to its bioinertness. To overcome this drawback, various studies have described surface coating approaches aimed at increasing the bioactivity of PEEK surfaces. Among those, it has been shown that the recently developed sol-gel TiO2 coating could provide PEEK with the ability to bond with bone tissue in vivo without the use of a bone graft. Objective This in vivo experimental study using a canine model determined the efficacy of bioactive TiO2-coated PEEK for anterior cervical fusion. Methods Sol-gel-derived TiO2 coating, which involves sandblasting and acid treatment, was used to give PEEK bone-bonding ability. The cervical interbody spacer, which was designed to fit the disc space of a beagle, was fabricated using bioactive TiO2-coated PEEK. Both uncoated PEEK (control) and TiO2-coated PEEK spacers were implanted into the cervical intervertebral space of beagles (n = 5 for each type). After the 3-month survival period, interbody fusion success was evaluated based on μ-CT imaging, histology, and manual palpation analyses. Results Manual palpation analyses indicated a 60% (3/5 cases) fusion (no gap between bone and implants) rate for the TiO2-coated PEEK group, indicating clear advantage over the 0% (0/5 cases) fusion rate for the uncoated PEEK group. The bony fusion rate of the TiO2-coated PEEK group was 40% according to μCT imaging; however, it was 0% of for the uncoated PEEK group. Additionally, the bone-implant contact ratio calculated using histomorphometry demonstrated a better contact ratio for the TiO2-coated PEEK group than for the uncoated PEEK group (mean, 32.6% vs 3.2%; p = 0.017). Conclusions The TiO2-coated bioactive PEEK implant demonstrated better fusion rates and bone-bonding ability than did the uncoated PEEK implant in the canine anterior cervical fusion model. Bioactive PEEK, which has bone-bonding ability, could contribute to further improvements in clinical outcomes for spinal interbody fusion.